2021
DOI: 10.21603/2308-4057-2021-1-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis products from sockeye (Oncorhynchus nerka L.) heads from the Kamchatka Peninsula produced by different methods: biological value

Abstract: Introduction. Sockeye salmon (Oncorhynchus nerka L.) is a valuable Pacific salmon. Sockeye heads are a significant share in processing sockeye salmon. Traditionally, fish by-products are used to make fishmeal. However, due to the high content of collagen proteins and fat in sockeye salmon heads, it is difficult to produce fishmeal from this raw material. Controlled enzymatic or combined hydrolysis allows protein, fat, and minerals to be extracted to supply the market with higher value products with desirable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Proteins are one of the most valuable components in fish heads [23]. The obtained FPHs had a higher protein content compared to other studies, which reported the protein contents of different fish protein hydrolysates to be between 50% and 90% [24][25][26][27][28]. However, they were in accordance with previous results on cod heads [7,8].…”
Section: Speciessupporting
confidence: 88%
“…Proteins are one of the most valuable components in fish heads [23]. The obtained FPHs had a higher protein content compared to other studies, which reported the protein contents of different fish protein hydrolysates to be between 50% and 90% [24][25][26][27][28]. However, they were in accordance with previous results on cod heads [7,8].…”
Section: Speciessupporting
confidence: 88%
“…A high number of studies have been carried out on the properties and potential uses of fish side-streams and by-products during the last decade (Table 1). Studies in the latest years include Sockeye heads [96]; Atlantic cod backbones; Atlantic salmon backbones/frames [66,97]; salmon viscera [62,98]; Atlantic salmon heads, frames, and viscera [66,99,100]; rainbow trout heads [101]; rainbow trout byproducts [102]; mackerel heads, frames, and viscera [103]; fish waste [104]; heads, skins, and bones from fish discards [17]; heads and bone frames from catfish [105]; viscera from red tilapia [106]; squid byproducts [107]; and frame and head from tilapia [108].…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%